The programmes of the Greek Catholic clergy of Northeastern Hungary (1860–1867) - Molnar Fedir; Molnár Ferenc; Молнар Федір (My University, 2022)
Abstract. The article addresses the problem of religious and political activity of the Greek Catholic clergy of Northeastern Hungary between 1860 and 1867. Considerable attention is paid to analyze the role of the local Rusyn leaders. Among the nationalities of the Hungarian Kingdom in the ХІХ century, the Rusyns were considered to be the poorest people, both materially and culturally. Their society was truncated, in other words, incompletely structured, consisting of the vast majority of peasants. The author highlights that in the absence of nobility and citizenry, their Greek Catholic clergy served as elites. Their ecclesiastical organization provided an appropriate framework and base for the development of their national culture and literature. The most signifi cant ecclesiastical structure of the Rusyns in Northeastern Hungary was the Greek Catholic Eparchy of Mukachevo, which had jurisdiction over seven Hungarian counties (Zemplén, Ung, Bereg, Ugocsa, Máramaros, Szabolcs and Szatmár). The current bishop of the diocese resided in Uzhhorod was the number one leader of the Rusyns. It is alleged that the so-called October Diploma, enacted by Austrian Emperor Franz Joseph on October 20, 1860, proclaimed a return to constitutional principles. On the basis of analysis of the various programmes of the Greek Catholic priests of the Eparchy of Mukachevo, it is established that the October Diploma had a great impact on the Rusyns of Hungary. This time, Adolf Dobriansky, a councillor of Hungary’s Lieutenancy Council claims the federal transformation of Hungary, the establishment of an independent Rusyn congress and a Greek Catholic archbishopric. As noted, his ideas also infl uenced many Rusyn priests. The traditionally pro-Hungarian Bishop of Mukachevo, Vasyl Popovych and his followers rejected Dobriansky’s ideas because of their «radical» nature. Instead, the Consistory of Uzhhorod wanted to accept nationality demands exclusively in cooperation with the Hungarian Parliament. The author comes to the conclusion that after the Austro-Hungarian Compromise of 1867, the pro-Hungarian Greek Catholic clergy of the Eparchy of Mukachevo was satisfi edwith the rights enshrined in the Nationalities Law of 1868. In the end it is revealed that the clergy believed: the state subsidies of the Diocese of Mukachevo would have been at risk by claiming nationality rights. The article summarizes the new material on the topic under study, introduces it into scientific circulation.

Резюме. Розглянуто проблему релігійної та політичної діяльності греко-католицького духовенства Північно-Східної Угорщини в 1860–1867 рр. Значну увагу приділено аналізу ролі місцевих русинських лідерів. Зазначено, що у ХІХ ст. із-поміж народів Угорського королівства найбіднішим етносом як у матеріальному плані, так і в контексті культурних здобутків вважали русинів; соціальна структура цієї спільноти була неповною, адже більшість становили неписьменні селяни. Стверджено, що за відсутності власного дворянства та буржуазії роль еліти відігравало греко-католицьке духовенство, а базою, зокрема фінансовою, для розвитку руської національної культури та літератури стали церковні структури. Встановлено, що найбільш значною церковною структурою русинів Північно-Східної Угорщини вважалася Мукачівська греко-католицька єпархія, чия влада поширювалася на сім угорських комітатів (Земплін, Унг, Берег, Угоча, Марамарош, Саболч і Сатмар), а єпископ, який керував єпархією з осідком в Ужгороді, – провідним лідером русинства. Стверджено, що Жовтневий диплом, який проголосив австрійський імператор Франц Йосиф І 20 жовтня 1860 р., ознаменував повернення до конституційних принципів. На підставі аналізу різних програм греко-католицьких священників Мукачівської єпархії встановлено, що Жовтневий диплом мав великий вплив на угорських русинів; у цей період радник Придворної ради Угорщини Адольф Добрянський відстоював федералізацію Угорщини, створення самостійного руського конгресу та греко-католицької архиєпархії. Зазначено, що його ідеї вплинули на багатьох руських священників. Констатовано, що проугорський мукачівський єпископ Василь Попович і його послідовники відхилили пропозиції Добрянського, оскільки вважали їх занадто радикальними, натомість ужгородська консисторія хотіла втілити національні потреби винятково у взаємодії з Державними зборами Угорщини. Висновано, що після австрійсько-угорської угоди 1867 р. дружнє до угорців греко-католицьке духовенство Мукачівської єпархії задовольнилося тими правами, які забезпечував Закон про національності від 1868 р. На закінчення зазначено, що духовенство побоювалося, що вимога розширення національних прав призведе до зменшення державного фінансування (субсидії) Мукачівської єпархії.
Програми Греко-Католицького духовенства Північно-СхідноЇ Угорщини (1860–1867)
Keywords: Greek Catholic Eparchy of Mukachevo; Rusyn clergy; Adolf Dobriansky; Northeastern Hungary; nationality question